Development of the flapping wing for ornithopters: a numerical modelling. Issue 1 (31st December 2022) - Mahendran, S.; Asokan, R.; Kumar, Ashutosh; Ria, Vitika; Jayadeep, S.
Abstract : To understand the working principle of ornithopters, various surveys were made on the natural flyers with flapping wings and their ability to produce lift and thrust. The crank mechanism is chosen to make the micro air vehicle (MAV) for spy work without being identified. This mechanism is one of the most complex ones, as its flow condition changes along with its wing motion. The flapping wing mechanism is analysed at two different speeds: 3 and 6 m/s. To analyse the aerodynamic characteristics, the lift and drag coefficient is measured at a different angle of attack using ANSYS software. The results are compared at various times with different working conditions to get the most suitable and reliable conditions. The designed flapping wings exhibit more efficiency with speed 6 m/s and the angle of attack at 15°.